Organometallics in synthesis third manual - Schlosser, M. (Manfred) (Wiley, 2013)
"Organometallics in Synthesis: A Manual, Third Edition is an essential resource for all synthetic organic chemists. The content and topics covered are completely new from the Second Edition, with an eye towards providing the most useful and practical reference on organometallics for practicing researchers. Background information about the organometallic class, the various methods to prepare organometallic compounds, and their use in synthetic reactions are coupled with mechanistic considerations and future research opportunities for each organometallic class. Interspersed throughout are hands-on, practical examples of the preparation of organometallics and their applications in organic synthesis - these are easy to follow with a recipe-like format, all thoroughly referenced to the primary literature"--